1999
DOI: 10.1128/jcm.37.12.3828-3834.1999
|View full text |Cite
|
Sign up to set email alerts
|

Identity of a Novel Swine Hepatitis E Virus in Taiwan Forming a Monophyletic Group with Taiwan Isolates of Human Hepatitis E Virus

Abstract: Recently, we found that more than 10% of the cases of acute non-A, non-B, non-C hepatitis in Taiwan were caused by a novel strain of hepatitis E virus (HEV). Since none of these patients had a history of travel to areas where HEV is endemic, the source of transmission remains unclear. The recent discovery of a swine HEV in herd pigs in the United States has led us to speculate that HEV may also circulate in herd pigs in Taiwan and may serve as a reservoir for HEV in Taiwan. Of 275 herd pigs obtained from 10 pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
89
0
3

Year Published

2002
2002
2010
2010

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 231 publications
(99 citation statements)
references
References 50 publications
(88 reference statements)
7
89
0
3
Order By: Relevance
“…Hepatitis E is an important disease of public health concern due to its zoonotic character. HEV has been widely reported to infect domestic swine herds around the world (Clayson et al, 1995;Meng et al, 1997Meng et al, , 1999Chandler et al, 1999;Hsieh et al, 1999;Pina et al, 2000). HEV transmission from wild animals to humans has been reported due to the consumption of raw or under-cooked deer or wild boar meat (Matsuda et al, 2003;Tei et al, 2003;Li et al, 2005).…”
Section: Hepatitis Ementioning
confidence: 99%
“…Hepatitis E is an important disease of public health concern due to its zoonotic character. HEV has been widely reported to infect domestic swine herds around the world (Clayson et al, 1995;Meng et al, 1997Meng et al, , 1999Chandler et al, 1999;Hsieh et al, 1999;Pina et al, 2000). HEV transmission from wild animals to humans has been reported due to the consumption of raw or under-cooked deer or wild boar meat (Matsuda et al, 2003;Tei et al, 2003;Li et al, 2005).…”
Section: Hepatitis Ementioning
confidence: 99%
“…Studies have shown that these strains are very closely related to the human viruses and that they productively infect primates (Meng et al, 1997(Meng et al, , 1998. Phylogenetic analysis indicates that swine viruses are more closely related to their human counterparts within a country than to other swine isolates around the world (Meng et al, 1997;Hsieh et al, 1999;van der Poel et al, 2001;Pei and Yoo, 2002;Nishizawa et al, 2003;Banks et al, 2004). Zoonotic transmission of this virus to the human population has been postulated to occur through the consumption of raw or lightly cooked meat from a naturally infected animal (Teo, 2006;Vasickova et al, 2007).…”
Section: Hepatitis E Virusmentioning
confidence: 99%
“…Hepatitis E virus, a member of the genus Hepevirus under the family Hepeviridae, has caused several outbreaks in developing countries and has prevalence in developed countries. HEV is transmitted predominantly by a fecal-oral route (Aggarwal and Krawczynshi, 2000;Hsieh et al, 1999); its prevalence is mainly waterborne. HEV is transmitted across species in humans, pigs, deer and rodents, and can cause experimental infection in chickens, cats and nonhuman primates (Arankalle et al, 2001;Feagins et al, 2008;Gardner and Luciw, 2008;Okamoto et al, 2004;Tei et al, 2003;Vitral et al, 2005).…”
Section: Introductionmentioning
confidence: 99%